Effectiveness and safety of four different beta‐blockers in patients with chronic heart failure. Issue 1 (6th January 2023) - Liu, Baoshan; Zhang, Rui; Zhang, Aiyuan; Wang, Guodong; Xu, Jiupan; Zhang, Yun; Liu, Yanping; Hao, Panpan
Abstract : In this study, we evaluated the effectiveness and safety of bisoprolol, metoprolol, carvedilol, and nebivolol in the treatment of chronic heart failure. The results demonstrated that bisoprolol improved the prognosis of chronic heart failure in comparison with carvedilol, and carvedilol exerted similar effects as metoprolol succinate and nebivolol and better effect than metoprolol tartrate (evidence levels: bisoprolol > carvedilol = metoprolol succinate = nebivolol > metoprolol tartrate; " > " means "prior to").